Usable Values of Nickel Ore and Nickel Concentrate Certified Reference Materials. Issue 2 (23rd October 2014) - Cheng, Zhizhong; Liu, Mei; Huang, Hongku; Gu, Tiexin; Yan, Weidong; Wen, Hongli
<x xml:space="preserve">Abstract</x> The preparation and characterisation of three nickel ores and two nickel concentrate certified reference materials are described in this paper. The samples of nickel ore and nickel concentrate were collected from the Hongqiling nickel deposit in Jilin province. The raw materials were crushed and passed through a 2.0‐mm sieve. The rough samples were then ground for 48 hr in a high‐alumina ball mill to a final size of < 0.074 mm. Homogeneity of the samples was tested by X‐ray fluorescence spectrometry (WD‐XRF) and inductively coupled plasma‐atomic emission spectrometry (ICP‐AES). The relative standard deviations (RSD) of results on mass fraction measurements by WD‐XRF were < 1.0% m/m for eighteen components. F‐tests showed that all five samples were homogeneous. Nineteen laboratories contributed with measurement results (2127 in total) for the certification of mass fractions for twenty‐three elements and compounds. Twenty‐three components in the nickel ores and twenty components in the nickel concentrates were characterised as certified values, while the Ni mass fractions ranges from 0.1 to 9.02% m/m in these certified reference materials. These five samples were approved as national certified reference materials by the National Organisation of Reference Materials of China in 2012.